PENGEMBANGAN BOOKLET BERBASIS LINK SEBAGAI MEDIA PEMBELAJARAN PADAMATERI SISTEM KOLOID (Kelas XI SMA/MA) - Elsa Wahyuni; Rosa Murwindra; Jumriana Rahayu Ningsih (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2023)
This study aims to determine the feasibility of developing a link-based booklet as a learning medium for colloidal system materials for SMA/MA Class XI. This research method is research and development (Research and Development, R&D) with ADDIE development model which includes the stages of Analysis (Analyze), Planning (Design), Development (Development), Implementation (Implement), Evaluation (Evaluate). The data collection instrument used was through validation sheets of media experts, material experts, linguists, and student response sheets. The data analysis technique used is by calculating the percentage score of the validation assessment. The results showed that the link-based booklet learning media developed the appropriate categories of media experts by 91.66%, material experts by 87.77% and language experts by 89.58%. This learning media also the appropriate category of student responses with a percentage of 90.18%. So that the development of a link-based booklet on colloidal system material for SMA/MA class XI is categorized as feasible as a learning medium.